Implementation of Rheumatic Excercise in Reducing Joint Pain among Elderly with Rheumatoid Arthritis at Public Health Center - Limbong, Magdalena; Olivia, Olivia; Nurhayati, Nurhayati; Kasim, Erna (Genius Journal, 2024)
Introduction: Rheumatoid arthritis is a musculoskeletal disorder characterized by pain in the extremities and joints. Rheumatic exercises are one of the effective methods to alleviate pain in individuals with rheumatoid arthritis. Objective: This study aims to evaluate the implementation of rheumatic exercises in reducing joint pain among elderly patients with rheumatoid arthritis at the Maccini Sawah Makassar Community Health Center. Method: A descriptive case study approach was conducted involving elderly participants meeting the inclusion criteria: willingness to participate, mild-to-moderate pain levels, and ability to engage in rheumatic exercises. Exclusion criteria included severe pain, stroke complications, or reliance on walking aids. The exercise regimen comprised warm-up, rheumatic exercises, and cool-down movements, lasting 25 minutes per session. Results: Findings revealed that three consecutive days of rheumatic exercises reduced joint pain in two respondents. Conclusion: Rheumatic exercises effectively reduce joint pain in patients with rheumatoid arthritis.